(untitled) (Research, Society and Development, 2022)
Implemented in Higher Education Institutions (HEIs) for some years, the monitoring activity is understood as a pedagogical resource to strengthen the teaching and learning process through the establishment of new pedagogical and experiential practices and experiences. In this work we aim, through an integrative review, to describe the monitoring activity of human anatomy in the process of teaching and student learning. The PICo strategy was used to form the guiding question, the results were presented through the Prisma Flow diagram. The databases consulted were Scielo, Portal Capes and Google Scholar, searching for articles from 2011 to 2021. Our results show that in addition to generating a strengthening of learning, the monitoring activity provides an incentive for teaching and is a collaborative and cooperative moment. between peers making the teaching and learning process active. In the search for a more critical and reflective professional future for the demands of today’s world.